2018
DOI: 10.1002/jor.24016
|View full text |Cite
|
Sign up to set email alerts
|

High glucose‐induced excessive reactive oxygen species promote apoptosis through mitochondrial damage in rat cartilage endplate cells

Abstract: Diabetes mellitus (DM) is an important factor in intervertebral disc degeneration (IDD). Apoptosis of cartilage endplate (CEP) cells is one of the initiators of IDD. However, the effects of high glucose on CEP cells are still unknown. Therefore, we conducted the present study to evaluate the effects of high glucose on CEP cells and to identify the mechanisms of those effects. Rat CEP cells were isolated and cultured in 10% foetal bovine serum (FBS, normal control) or high-glucose medium (10% FBS + 0.1 M glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 25 publications
5
49
0
Order By: Relevance
“…In addition, our results also showed a positive dose-effect relationship between glucose concentration and AF cell apoptosis. In line with us, several studies also showed that high glucose promotes disc cell apoptosis, such as CEP cells and notochordal cells [20,21]. Hence, inhibiting high glucose-induced disc cell apoptosis may be an effective strategy to retard disc degeneration in DM patients.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In addition, our results also showed a positive dose-effect relationship between glucose concentration and AF cell apoptosis. In line with us, several studies also showed that high glucose promotes disc cell apoptosis, such as CEP cells and notochordal cells [20,21]. Hence, inhibiting high glucose-induced disc cell apoptosis may be an effective strategy to retard disc degeneration in DM patients.…”
Section: Discussionsupporting
confidence: 67%
“…Recently, some epidemiological studies have demonstrated that diabetes facilitates disc degeneration, and DM patients have a higher incidence of disc degeneration than non-DM patients [3,[27][28][29]. Several basic researches have investigated the responses of disc cells to high glucose treatment and reported that high glucose significantly promotes senescence of disc NP cells, notochordal cells and AF cells [17][18][19], and induces apoptosis of disc CEP cells and notochordal cells [20,21]. However, the effects of high glucose on AF cell apoptosis are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the endplate capillaries are responsible for supplying nutrients to the intervertebral discs, degeneration of the endplates is thought to be a risk factor for IDD, as it can hinder the transport of nutrients and eventually lead to IDD (6)(7)(8). Therefore, CEPs may be particularly susceptible to the vasculopathy associated with dM and increasing evidence has revealed that dM plays an important role in ceP degeneration (2,(9)(10)(11)(12). Fields et al revealed that endplate sclerosis, increased endplate thickness and decreased endplate porosity were observed in rats with type 2 diabetes (9).…”
Section: Introductionmentioning
confidence: 99%
“…Fields et al revealed that endplate sclerosis, increased endplate thickness and decreased endplate porosity were observed in rats with type 2 diabetes (9). Furthermore, high-glucose was revealed to induce the apoptosis of rat cartilage endplate cells in a dose-and time-dependent manner (12).…”
Section: Introductionmentioning
confidence: 99%